2022
DOI: 10.1002/hbm.25985
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of childhood maltreatment and subtypes with personalized functional connectome of large‐scale brain networks

Abstract: Childhood maltreatment (CM) has a long impact on physical and mental health of children. However, the neural underpinnings of CM are still unclear. In this study, we aimed to establish the associations between functional connectome of large‐scale brain networks and influences of CM evaluated through Childhood Trauma Questionnaire (CTQ) at the individual level based on resting‐state functional magnetic resonance imaging data of 215 adults. A novel individual functional mapping approach was employed to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…Indeed, many fields, from oncology and cardiology to internal medicine, have developed biomarkers that indicate specific pathophysiological mechanisms. In recent years, the combination of machine‐learning‐based MVPA approaches and neuroimaging data features has yielded some encouraging diagnostic and predictive models for individual‐level disease diagnosis and efficacy prediction (H. Li et al, 2022 ; Pang et al, 2022 ; Zhang et al, 2022 ). However, it is still in the early stages of brain biomarker development; future applications should extend our predictive model to multiple time‐visits longitudinal experimental designs, such as predicting the effect of pharmacological and non‐pharmacological therapies on insomnia by collecting data from two time points observed before and after treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, many fields, from oncology and cardiology to internal medicine, have developed biomarkers that indicate specific pathophysiological mechanisms. In recent years, the combination of machine‐learning‐based MVPA approaches and neuroimaging data features has yielded some encouraging diagnostic and predictive models for individual‐level disease diagnosis and efficacy prediction (H. Li et al, 2022 ; Pang et al, 2022 ; Zhang et al, 2022 ). However, it is still in the early stages of brain biomarker development; future applications should extend our predictive model to multiple time‐visits longitudinal experimental designs, such as predicting the effect of pharmacological and non‐pharmacological therapies on insomnia by collecting data from two time points observed before and after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…from oncology and cardiology to internal medicine, have developed biomarkers that indicate specific pathophysiological mechanisms. In recent years, the combination of machine-learning-based MVPA approaches and neuroimaging data features has yielded some encouraging diagnostic and predictive models for individual-level disease diagnosis and efficacy prediction (H Li et al, 2022;Pang et al, 2022;Zhang et al, 2022)…”
mentioning
confidence: 99%
“…Cui and colleagues found that variability of brain functional topography is highly correlated to evolutionary expansion, cortical myelination, and cerebral blood ow (Cui et al, 2020). Recently, we found that individual functional connectivity could effectively predict personalized childhood maltreatment and subtype levels (Zhang et al, 2022). These studies indicated that individualspeci c functional connectivity mapping outperforms group-level methods to better capture cognitions and behaviors.…”
Section: Edge-centric Time Series Analysismentioning
confidence: 82%
“…Cognitive emotion dysregulation is a potential mechanism by which childhood trauma experience increases risk of anxiety (Huh et al, 2017 ). According to previous resting‐state fMRI studies of large‐scale brain networks, childhood trauma is associated with atypical neural networks involved in perceptual, cognitive, and emotional regulation systems (Zhang, Zhao, et al, 2022 ). Further evidence suggests that childhood trauma experiences may alter plasticity processes and affect the regular functional interaction of cortical and subcortical neural networks.…”
Section: Discussionmentioning
confidence: 99%